Can't we all just get along?. - Cass, S. (IEEE spectrum)
Now the push is on to move beyond simply exchanging data and to allow software applications to employ other applications in the same way that a person might use multiple programs to achieve a task. For example, a person has no problem using a Web browser to download an image, another program to sharpen the image, and finally an e-mail program to send the image to someone else. This effort to expose functionality has ultimately resulted in plans to create so-called Web services These plans originated as companies tried to figure out distributed computing, which spreads heavy computational tasks over multiple computers in a network and yet makes the results appear to the end user as if they were the product of running an application on a single, superpowerful machine.